Relationship of angiopoietin-2 level with the prognosis of the COVID-19 disease - Keskin, Olgun; Kalan Sari, Işılay; Seremet Keskin, Aysegul; Ellidağ, Hamit Yaşar; Harmandar, Orbay (The Journal of Infection in Developing Countries, 2023)
Introduction: COVID-19 infection is associated with coagulopathy. There is increased expression of markers such as E-selectin or angiopoietin-2 upon the activation of endothelin. The aim of this study was to determine whether there was a difference in angiopoietin-2 levels among patients with a diagnosis of COVID-19 who need to be hospitalized in the intensive care units (ICUs) or service. Methodology: COVID-19 infected patients admitted in the hospital were included in this study. In addition to the routine biochemical parameters of patients in ICUs and services, 5 cc blood samples were collected and angiopoietin-2 was analyzed. Demographic data of the patients, biochemical parameters at the time of hospitalization, places and durations of hospitalization as well as their ways of being discharged from hospital were recorded. Results: 180 patients who presented to our hospital’s emergency service and were hospitalized with a diagnosis of COVID-19 were included in our study. 137 patients (76.1%) were hospitalized in the service and 43 (23.9%) were hospitalized in ICU. The angiopoietin-2 level was determined to be significantly high in the patients hospitalized in ICUs (p = 0.018). When the cut-off value of angiopoetin-2 in predicting the ICU hospitalization was assumed as 64.5 ng/L, its sensitivity was determined to be 59% and its specificity was found to be 42%. Conclusions: We concluded that angiopoietin-2 level in COVID-19 patients upon their presentation to the hospital might be an important parameter in predicting and ascertaining their place of hospitalization.